Assessing Information Literacy Skills of Mathematics Faculty Members in Pakistan - Malik, Amara; Ali, Shahbaz; Batool, Hina; Ameen, Kanwal (Qualitative and Quantitative Methods in Libraries; Vol 10 No 3 (2021): September issue 2021, 2021)
Information literacy (IL) skills comprise the set of competencies, which are useful for research, lifelong learning and to become the critical consumer of information in 21 st century. The present study aimed to assess IL skills of mathematics faculty members in higher education institutes of Pakistan. The study explored their ability to identify the information need and sources; to plan strategies for locating, accessing, evaluating and ethically applying the needed information effectively and efficiently. The study employed a quantitative research approach and structured questionnaire based on SCONUL Seven Pillars of Information Literacy, was sent to 300 faculty members from 36 HEC recognized public sector universities of the Punjab province. After repeated follow up calls, 185 filled questionnaires were received. The data were analyzed using SPSS-24. The major findings of the study showed that the mathematics faculty members had reasonable IL skills of basic level. They were able to identify information need and related information sources. They were able to scope, plan, gather, evaluate, manage and present information legally and ethically. However, they were less competent at the advanced level of IL skills. The study suggested that information professionals/librarians working in university libraries should design need-based IL programs to cater the needs of faculty members.